STRATEGI GURU DALAM PENANAMAN KEDISIPLINAN DAN KEJUJURAN PESERTA DIDIK DI MI DDI ANCE KECAMATAN TANETE RILAU KABUPATEN BARRU: Teacher Strategies In Incorporating Discipline And Honesty In Students At Mi Ddi Ance, Tanete Rilau District, Barru Regency - Darmawati; Imran Saputra (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study discusses teachers’ strategies in instilling discipline and honesty in students, as well as the inhibiting and supporting factors at MI DDI Ance, Tanete Rilau Subdistrict, Barru Regency. The research employed a phenomenological approach. The main research instrument was the researcher, supported by data collection tools in the form of interview guidelines. Data were collected through observation, interviews, and documentation, while the validity of the findings was tested using data source triangulation and theory triangulation. The results show that teachers’ strategies include role modeling, habituation, positioning themselves as the main examples in the school, and giving sanctions. Teachers also provide continuous instruction to students, habituate them to act honestly, and conduct honesty reflections as core strategies. The inhibiting factors in instilling discipline and honesty among students are family environment, lack of interest or awareness from the students themselves, and low levels of intelligence. On the other hand, the supporting factors include supervision from the school principal, direct teacher involvement with students, strong teamwork among teachers, gradual delivery of knowledge and understanding, role modeling, giving advice and motivation, as well as habituation practices.